Seven lessons for financial incentivisation schemes in healthcare: a qualitative study of NHS Resolution’s Maternity Incentive Scheme - Graham Paul Martin; Gizdem Akdur; Jane O’Hara; Mary Dixon-Woods (Journal of the Royal Society of Medicine, 2026)
Objectives: Avoidable harm and variations in quality have remained persistent features of health systems, but the track record of financial incentives in driving improvement is mixed. Based on an evaluation of NHS Resolution’s Maternity Incentive Scheme (MIS), which focuses on safety of maternity care in English NHS trusts, we identify generalisable principles to inform design of financial incentive schemes in healthcare. Design: Qualitative process evaluation based on interviews with those involved in the design and delivery of MIS. Setting: Organisations involved in running MIS and organisations participating in the scheme. Participants: Thirty-five individuals were interviewed, including 17 involved in the national-level administration of MIS and 18 with experience of MIS at local level. Main outcome measures: Not applicable. Results: We identified strengths, weaknesses and unintended consequences of the Scheme from the perspective of participants. MIS was seen by national-level stakeholders as having succeeded in elevating maternity safety in organisations’ priorities and consolidating disparate safety requirements into a unified framework. They saw MIS as a clinically credible and system-owned mechanism for prioritisation. However, local-level participants reported significant administrative burdens, opportunity costs and challenges in interpreting and implementing its requirements. The Scheme’s all-or-nothing reimbursement model, while reinforcing parity across the areas it covered, sometimes led to disproportionate focus on marginal issues and created perverse incentives when full compliance seemed unattainable. We identify seven key lessons for the design of incentive systems that might optimise their impact from the findings. Conclusions: Careful design of incentive schemes is vital to minimise unintended consequences. Lessons from MIS are relevant to broader healthcare system reform efforts and initiatives aiming to harness financial levers for quality improvement, such as those in the 10-Year Health Plan for England.